Pelatihan Penggunaan E-Commerce Sebagai Upaya Pemasaran Penjualan Produk Kerajinan Rumah Tangga Ibu-ibu PKK Desa Perkebunan Limau Manis, Kabupaten Batubara - Yessica Siagian; Arridha Zikra Syah; Muhammad Amin; Wan Mariatul Kifti (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
This community service activity was expected to add knowledge of PKK ladies. The knowledge of how to use the e-commerce, marketplaces and social media were regarding the marketing of household handicraft products more effectively and efficiently. This community service activity was conducted for 2 (two) days, namely on February 26 and 27, 2021 at the village hall of Limau Manis Batubara plantation, with different materials. The training was conducted in accordance with the agreement between the implementing team and the PKK group of Limau Manis Batubara plantation village. At this stage, the PKK group of Limau Manis Batubara plantation village can directly practice applying the material delivered. Then the team provides assistance to monitor the progress of marketing activities on the app account that has been created during training. Participants can interact directly or through chat messages with the organizing team if there were difficulties in operation. The participants in this community service activity werw the ladies of pkk group members of Limau Manis Batubara plantation village. This training activity can be used as a medium for participants to be able to participate and be directly involved in utilizing communication media in the digital age